Evolution of pore structure and fractal characteristics during hydrate-based CO2 sequestration in unconsolidated sediments - Zhun Zhang; Yuning Liu; Yunkai Ji; Jiaxian Wang; JinQiu Hu; Bin Fang; Wanjun Lu; Changling Liu; Fulong Ning (Chemical Engineering Journal, 2026)

Formation and application of soybean protein amyloid fibril-dextran-epigallocatechin gallate nanoparticles for interfacial engineering of lycopene-loaded Pickering emulsions - Changling Wu; Jie Hou; David Julian McClements; Li Li; Zhaogui Chen; Chengjun Liao; Kaixi Chen; Guangbiao Yan; Hao Hu; Guanyu Fang; Zhiping He; Xingquan Liu; et al. (Food Chemistry, 2026)

Pronounced seasonality and eutrophication-driven dominance of Gephyrocapsa oceanica in Bohai Bay: A baseline assessment of living coccolithophores under anthropogenic pressure - Jiayao Shen; Haijiao Liu; Changling Ding; Jun Sun (Marine Environmental Research, 2026)

Formation and application of soy protein/modified chitosan nanoparticles for interfacial engineering of β-carotene-loaded Pickering emulsions - Shuaizheng Wang; David Julian McClements; Yijun Zuo; Qinqin Lan; Jie Hou; Yishu Gao; Hao Hu; Pengxiao Wang; Peng Wang; Xingquan Liu; Changling Wu (Food Chemistry, 2026)

Formation of ι-carrageenan-mediated complex: Enhancing thermal stability of α-amylase inhibitor from white kidney bean - Xine Huang; Yizhou Xiang; Xiaoning Zhu; Chenjuan Zeng; Liang Zou; Lei Wang; Changling Wu; Xingquan Liu; Zisheng Luo; Li Li (Food Hydrocolloids, 2026)

Hydrochemical characteristics, controlling mechanisms and quality evaluation of mine water in Jinjie coal mine, Yushen Coalfield, Northwest China: a combined statistical and hydrogeochemical study - Ji Liu; Min Gao; Xing Liu; Changling Ma; Hua Liu (Carbonates and Evaporites, 2026)

Natural gas hydrate morphology evolution and resistivity response during thermal dissociation in porous media - Yongge Liu; Yipu Li; Jianxin Liu; Jian Hou; Zezheng Sun; Bin Fang; Yuechao Zhao; Qingjun Du; Yunkai Ji; Changling Liu; Bei Wei; Zhangxing Chen (Chemical Engineering Journal, 2026)

Analysis of shearing behavior in hydrate-bearing sediments from a micromechanical perspective: A DEM simulation study - Jiawei Zhang; Yongchao Zhang; Lele Liu; Lei Wang; Yanlong Li; Yunkai Ji; Bo Zou; Changling Liu (Geomechanics for Energy and the Environment, 2026)

Phytoplankton community responses to natural and anthropogenic nutrient inputs in the Western Pacific Ocean: Insight from chemical taxonomy analysis - Zishi Liu; Wenzhuo Yan; Yujian Wen; Changling Ding; Jun Sun (Marine Pollution Bulletin, 2026)

Phytoplankton and carbon biomass dynamics in the South China Sea: responses to shelf-oceanic gradients and tropical cyclone - Changling Ding; Xingzhou Wang; Yi Long; Zishi Liu; Jun Sun (Marine Life Science & Technology, 2026)

Encapsulation of quercetin in zein/sodium caseinate nanoparticles: Fabrication, characterization, stability and controlled release properties - Peng Wang; Jinxia Wang; Huimin Hu; Nike Ding; Fenghua Wu; Guanyu Fang; Jing Mao; Changling Wu; Xingquan Liu (Food Research International, 2026)

Network pharmacology research integrating LC–MS/MS, machine learning, molecular docking, and dynamics simulation: key biomarkers and potential mechanisms of Phellinus igniarius against prostate cancer - Zixuan Ren; Xiaohong Liu; Jihang Zhang; Min Song; Qingwen Yang; Changling Li; Deshan Liu (In Silico Pharmacology, 2026)

Vertical zonation and interaction patterns of heterotrophic protists in the Bay of Bengal and Eastern Indian Ocean - Laxman Pujari; Qi Qiao; Sujata Nilajkar; Ting Gu; Danyang Li; Yiyan Guo; Xuelei Zhang; Lin Liu; Changling Ding; Jun Sun (Marine Pollution Bulletin, 2026)

Evolution characteristics of methane concentration and microscopic formation mechanisms of methane hydrate: Insights from in-situ Raman spectroscopy - Xiaoqian Qiu; Yunkai Ji; Qingguo Meng; Qingtao Bu; Xiluo Hao; Changling Liu; Yapeng Zhao; Jianye Sun; Qi Li; Gaowei Hu (Gas Science and Engineering, 2026)

High internal phase emulsions stabilized by soybean protein amyloid fibril-dextran-epigallocatechin gallate composites: Formation, stability, and properties - Jie Hou; David Julian McClements; Yijun Zuo; Shuaizheng Wang; Bohui Ma; Lan Qinqin; Fenghua Wu; Peng Wang; Xingquan Liu; Changling Wu (Food Hydrocolloids, 2026)

Ultrasonic-assisted deep eutectic solvents extraction of saponins from Strobilanthes sarcorrhiza: Process optimization and mechanistic insights - Peng Wang; Kaijun Wang; Tiantian Li; Shilin Zhang; Jiang Wu; Fenghua Wu; Guanyu Fang; Changling Wu; Xingquan Liu (Chemical Engineering Journal, 2026)

Enhanced quality retention and flavor integrity of Camellia oleifera C.Abel seeds oil: Ultrasound-assisted moderate refining strategy - Suikang Yuan; Guanyu Fang; Changling Wu; Zhehua He; Weiping Zheng; Xingquan Liu; Peng Wang; Fenghua Wu (Food Chemistry, 2026)

Predicting heat-induced hazardous compounds in roasted almonds via browning index and moisture using machine learning - Yunhao Xia; Buyu Liu; Kaijun Wang; Zhongwu Yu; Wenhan Yan; Changling Wu; Guanyu Fang; Fenghua Wu; Xingquan Liu; Peng Wang (Food Chemistry, 2026)

Experimental and hypoplastic model investigation of frozen soil mechanics: Integrating confining pressure, temperature, and ice content effects - Jiawei Zhang; Yongchao Zhang; Ke Ke; Lilin Li; Yanlong Li; Lele Liu; Changling Liu; Nengyou Wu (Cold Regions Science and Technology, 2026)

Fabrication, characterization, and application of walnut protein-polyphenol conjugates as nano emulsifier in oil-in-water emulsions - Changling Wu; Bohui Ma; David Julian McClements; Zhengjia Wang; Shuaizheng Wang; Jie Hou; Yijun Zuo; Qinqin Lan; Peng Wang; Fenghua Wu; Weiping Zheng; Xingquan Liu (Food Chemistry, 2025)

Anthropogenic elemental fluxes from wastewater treatment plants to urban rivers: Quantifying emission contributions in Guiyang - Jianping Zhu; Qixin Wu; Meixue Peng; Shilin Gao; Jie Zeng; Changling Liu; Hao Xia (Environmental Research, 2025)

Advances in emerging two-dimensional nanomaterials: Design strategies, structural engineering, and applications in food - Wanfeng Wu; Tuck-Whye Wong; Xingquan Liu; Changling Wu; Nannan Dong; Mengyun Tu; Jingjing Zhou; Yaoqi Zhang; Mengfei Mao; Tiefeng Li; XuXu Yang; Li Li (Trends in Food Science & Technology, 2025)

A deep learning framework for mitigating agricultural pollution: Quantifying and managing herbicide drift risk to non-target crops from UASS spraying - Huiyuan Zhang; Tongye Shi; Xiaofu Feng; Ziyan Liu; Zhaoyan Zhu; Mengran Yang; Changling Wang; Xiongkui He (Journal of Cleaner Production, 2025)

Regulation of aerobic methane oxidation by methane concentration: insights from cultivation experiments - Qikun Tian; Yu Zhen; Jing Li; Xiaoqing Xu; Changling Liu (Acta Oceanologica Sinica, 2025)

Analytical and Experimental Technology for Marine Gas Hydrate - Changling Liu; Qiang Chen (Journal of Marine Science and Engineering, 2025)
Analytical and Experimental Technology is an essential and important means for basic theoretical research on marine natural gas hydrates [...]

Effect of chitosan coating on the characterization and stability of the CPH liposomes - Peng Wang; Shuqing Zhu; Qiaonan Zhu; Xuan Yang; Changling Wu; Kaiyun Liang; Zhehua He; Weihong Min; Xingquan Liu; Weirong Li; Fenghua Wu (Journal of Food Engineering, 2025)

Mechanical properties of gas hydrate-bearing sediments: Research progress, challenges and perspectives - Yapeng Zhao; Gaowei Hu; Lele Liu; Changling Liu; Yizhao Wan; Qingtao Bu; Yunkai Ji; Zhun Zhang; Liang Kong (Earth-Science Reviews, 2025)

Experimental Analysis of Resistivity Logging Response of Marine Gas Hydrate Reservoirs - Qiang Chen; Chengfeng Li; Hongbin Wang; Changling Liu; Qingtao Bu; Jianye Sun; Jiangong Wei; Beibei Kou (Journal of Ocean University of China, 2025)

Explosion-puffing pretreatment effect on the microstructure of Camellia oleifera Abel. seed and the quality of its oil - Suikang Yuan; Fenghua Wu; Xuan Yang; Weihong Min; Zhehua He; Changling Wu; Xingquan Liu; Peng Wang (Food Chemistry, 2024)

Fractionation of phenolic compounds from hickory by-products using solid phase extraction-sonication: Chemical composition, antioxidant and antimicrobial activity - Changling Wu; Bohui Ma; David Julian McClements; Zhiquan Lai; Jie Hou; Shuaizheng Wang; Xinru Wang; Yuxin Qiu; Fenghua Wu; Guanyu Fang; Xingquan Liu; Peng Wang (Food Chemistry, 2024)

Dependence of the hydrate-based CO2 storage characteristics on sand particle size and clay content in unconsolidated sediments - Jiaxian Wang; Yunkai Ji; Changling Liu; Fulong Ning; Qingguo Meng; Yapeng Zhao; Jing Li; Zhun Zhang; Yongchao Zhang; Feng Cai (Chemical Engineering Journal, 2024)

Fungal fermentation improves the nutritional quality, flavor characteristic and physicochemical property of highland barley bran - Yongzhu Zhang; Mingxin Liu; Fenghua Wu; Jinmei Li; Fidelis Azi; Ke Yu; Zhiping He; Peng Wang; Changling Wu; Baiyi Lu; Xingquan Liu (Journal of Cereal Science, 2024)

Combined influence of the nanoplastics and polycyclic aromatic hydrocarbons exposure on microbial community in seawater environment - Xin Guan; Dai Jia; Xinyu Liu; Changling Ding; Jinfei Guo; Min Yao; Zhan Zhang; Mengxi Zhou; Jun Sun (Science of The Total Environment, 2024)

Molecular insights into the impact of mineral pore size on methane hydrate formation - Zhengcai Zhang; Guang-Jun Guo; Changling Liu; Nengyou Wu (Fuel, 2024)

Experimental Study on Consolidation Properties of Hydrate-Bearing Fine-Grained Sediments Collected from the Shenhu Area of the Northern South China Sea - Ruchun Wei; Lele Liu; Chao Jia; Xiao Dong; Qingtao Bu; Yongchao Zhang; Changling Liu; Nengyou Wu (Journal of Ocean University of China, 2024)

Analysis of permeability anisotropy of marine hydrate-bearing sediments using fractal theory combined with X-CT - Zhun Zhang; Zikun Li; Chengfeng Li; Zhuo Zhang; Changling Liu; Wanjun Lu; Fulong Ning (Ocean Engineering, 2024)

Pore-scale investigations of permeability of saturated porous media: Pore structure efficiency - Zhun Zhang; Zhuo Zhang; Wanjun Lu; Huirong Guo; Changling Liu; Fulong Ning (Journal of Hydrology, 2024)

Pore Water Conversion Characteristics during Methane Hydrate Formation: Insights from Low-Field Nuclear Magnetic Resonance (NMR) Measurements - Jiaxian Wang; Yunkai Ji; Changling Liu; Qingguo Meng; Yapeng Zhao; Zhun Zhang; Jianye Sun; Lele Liu; Fulong Ning (Journal of Marine Science and Engineering, 2024)
Understanding the conversion characteristics of pore water is crucial for investigating the mechanism of hydrate accumulation; however, research in this area remains limited. This study conducted methane hydrate formation experiments in unconsolidated sands using an in-house low-field nuclear magnetic resonance (NMR) system. It focused on pore water conversion characteristics and influencing factors such as initial water saturation and sand particle sizes. Results show that methane hydrate formation enhances the homogeneity of the effective pore structure within sand samples. The conversion rate of pore water is significantly influenced by differences in heat and mass transfer capacity, decreasing as initial water saturation and sand size increase. Pore water cannot be fully converted into hydrates in unconsolidated sands. The final conversion ratio of pore water in water-poor sand samples nears 97%, while in water-rich sand samples, it is only 65.80%. Sand particle size variation has a negligible impact on the final conversion ratio of pore water, with ratios exceeding 94% across different particle sizes, differing by less than 3%.

The pore-structure characteristics of foraminiferal shells and their relations with natural gas hydrate formation in the marine sediments - Yongchao Zhang; Lele Liu; Jing Li; Qiang Chen; Chengfeng Li; Jianye Sun; Changling Liu (Gas Science and Engineering, 2024)

Evaluation of the Shallow Gas Hydrate Production Based on the Radial Drilling-Heat Injection-Back Fill Method - Qiang Chen; Yizhao Wan; Nengyou Wu; Jianye Sun; Jian Wang; Changling Liu; Yanlong Li; Chengfeng Li; Gaowei Hu (Journal of Ocean University of China, 2024)

Dissolved and particulate heavy metal pollution status in seawater and sedimentary heavy metals of the Bohai Bay - Haijiao Liu; Changling Ding; Guicheng Zhang; Yiyan Guo; Yuyao Song; Satheeswaran Thangaraj; Xiaodong Zhang; Jun Sun (Marine Environmental Research, 2023)

Permeability of hydrate-bearing fine-grained sediments: Research status, challenges and perspectives - Zhun Zhang; Lele Liu; Wanjun Lu; Changling Liu; Fulong Ning; Sheng Dai (Earth-Science Reviews, 2023)

Undrained Triaxial Shear Tests on Hydrate-Bearing Fine-Grained Sediments from the Shenhu Area of South China Sea - Ruchun Wei; Lele Liu; Chao Jia; Xiao Dong; Qingtao Bu; Yongchao Zhang; Changling Liu; Nengyou Wu (Journal of Marine Science and Engineering, 2023)
Changes in undrained shear strength are important to the stability analysis of hydrate reservoirs during natural gas hydrate production. This study proposes a prediction model of undrained shear strength of hydrate-bearing fine-grained sediments based on the critical state theory. Several consolidated undrained triaxial shear tests are conducted on hydrate-bearing fine-grained samples from the Shenhu area of the South China Sea. The effects of effective consolidation stresses and hydrate saturations on the undrained shear strength are investigated. The results show that the undrained shear strength increases linearly with increasing effective consolidation stress. When the hydrate saturation is greater than the effective hydrate saturation, the undrained shear strength significantly increases with increasing hydrate saturation. The undrained shear strength of hydrate-bearing fine-grained sediments is a two-parameter function of effective hydrate saturation and a void ratio. The instability risk of the hydrate reservoir under undrained conditions is greater than that of under-drained or partially drained conditions. Furthermore, low-porosity reservoirs face more shear strength loss from hydrate decomposition yet lower risk than high-porosity ones. These results can improve the understanding of mechanical properties of hydrate-bearing fine-grained sediments under undrained conditions. This study also has implications for the design of marine structures in areas with hydrate-bearing sediment.

Hydrophyte Debris Induced Sedimentary Phosphorus Release in Tuojiang Rivers, China - Changling Liu; Xianfan Yuan; Yuqiong Li; Zhong Yang (Bulletin of Environmental Contamination and Toxicology, 2023)

Transitional traits determine the acclimation characteristics of the coccolithophore Chrysotila dentata to ocean warming and acidification - Satheeswaran Thangaraj; Haijiao Liu; Yiyan Guo; Changling Ding; Il‐Nam Kim; Jun Sun (Environmental Microbiology, 2023)
Ocean warming and acidification interactively affect the coccolithophore physiology and drives major biogeochemical changes. While numerous studies investigated coccolithophore under short‐term conditions, knowledge on how different transitional periods over long‐exposure could influence the element, macromolecular and metabolic changes for its acclimation are largely unknown. We cultured the coccolithophore Chrysotila dentata , (culture generations of 1st, 10th, and 20th) under present (low‐temperature low‐carbon‐dioxide [LTLC]) and projected (high‐temperature high‐carbon‐dioxide [HTHC]) ocean conditions. We examined elemental and macromolecular component changes and sequenced a transcriptome. We found that with long‐exposure, most physiological responses in HTHC cells decreased when compared with those in LTLC, however, HTHC cell physiology showed constant elevation between each generation. Specifically, compared to 1st generation, the 20th generation HTHC cells showed increases in quota carbon (Qc:29%), nitrogen (Q N :101%), and subsequent changes in C:N‐ratio (68%). We observed higher lipid accumulation than carbohydrates within HTHC cells under long‐exposure, suggesting that lipids were used as an alternative energy source for cellular acclimation. Protein biosynthesis pathways increased their efficiency during long‐term HTHC condition, indicating that cells produced more proteins than required to initiate acclimation. Our findings suggest that the coccolithophore resilience increased between the 1st–10th generation to initiate the acclimation process under ocean warming and acidifying conditions.

The impact of environmental factors on the phytoplankton communities in the Western Pacific Ocean: HPLC-CHEMTAX approach - Guicheng Zhang; Zishi Liu; Zhaoyi Zhang; Changling Ding; Jun Sun (Frontiers in Marine Science, 2023)
The distribution characteristics, biomass, and communities of phytoplankton in the western Pacific Ocean (WPO) were investigated using high-performance liquid chromatography (HPLC)-CHEMTAX analysis. The results revealed significant differences in the distribution of phytoplankton communities among different water masses in the WPO. Haptophytes were the dominant group, followed by Prochlorophytes, Cyanobacteria, Prasinophytes, and Diatoms. The distribution of phytoplankton communities was primarily determined by the level of nitrate, phosphate, and silicate, while temperature showed a negative correlation with major phytoplankton communities. In the 130°E section, the divergence caused by Halmahera Eddy (HE) and Mindanao Eddy (ME) provided the abundant nutrients, making them the primary environmental influence factor near the equator. This divergence brought relatively eutrophic deep seawater into the euphotic layer, resulting higher biomass of phytoplankton communities. In the 20°N section, the distribution of phytoplankton was mainly influenced by the invasion of Kuroshio Current and its offshore flow. Additionally, due to the low surface-to-volume ratios, microphytoplankton dominated the phytoplankton community in this section instead of nanophytoplankton or picophytoplankton. In summary, this study confirms previous findings on distribution characteristics of phytoplankton and provides new insights into the environmental and biological regulations of phytoplankton communities in the WPO.

Elastic wave velocity of marine sediments with free gas: Insights from CT-acoustic observation and theoretical analysis - Jie Chen; Gaowei Hu; Qingtao Bu; Nengyou Wu; Changling Liu; Qiang Chen; Chengfeng Li; Yizhao Wan; Zihao Wang; Wengao Zhao; Jiale Kang; Jiafang Xu (Marine and Petroleum Geology, 2023)

Longitudinal expression profiles of flavonoid synthesis-related genes and their correlations with contents of flavonoids including anthocyanins in purplish-green aerial stems of Panax notoginseng - Hongling Zhang; Guiqiong Li; Min Jiang; Changling Zhao; Pengyu Zhao; Chen Wang; Guosong Wen; Feng Zhou; Wenhua Dongchen; Shaozhong Xu; Ting Mu; Fanlai Meng; et al. (Acta Physiologiae Plantarum, 2023)

Improving pre-harvest sprouting resistance in rice by editing OsABA8ox using CRISPR/Cas9 - Kai Fu; Weihan Song; Cheng Chen; Changling Mou; Yunshuai Huang; Fulin Zhang; Qixian Hao; Ping Wang; Tengfei Ma; Yaping Chen; Ziyan Zhu; Min Zhang; et al. (Plant Cell Reports, 2022)

Hydrate formation and distribution within unconsolidated sediment: Insights from laboratory electrical resistivity tomography - Yanlong Li; Nengyou Wu; Changling Liu; Qiang Chen; Fulong Ning; Shuoshi Wang; Gaowei Hu; Deli Gao (Acta Oceanologica Sinica, 2022)

Effect of Hydrate Microscopic Distribution on Acoustic Characteristics during Hydrate Dissociation: An Insight from Combined Acoustic-CT Detection Study - Qingtao Bu; Tongju Xing; Chengfeng Li; Jinhuan Zhao; Changling Liu; Zihao Wang; Wengao Zhao; Jiale Kang; Qingguo Meng; Gaowei Hu (Journal of Marine Science and Engineering, 2022)
Geophysical detection techniques are important methods in marine gas hydrate exploration and monitoring, because the small-scale distribution of hydrates has a large impact on the wave velocity. The acoustic response characteristics of hydrate micro-distributions have strong significance for monitoring the hydrate dissociation process. In this paper, experiments simulating the hydrate dissociation process were carried out in a self-developed experimental device combining X-ray computed tomography (X-CT) scanning and ultrasonic detection, which allowed the acoustic wave characteristics and X-CT scanning results to be simultaneously obtained during the hydrate dissociation process. This study found that the hydrate dissociation stage is divided into three stages. The hydrate begins to dissociate at spots where it comes into touch with sand particles early in the dissociation process. The main factor affecting the acoustic wave velocity of hydrates in this stage is changes in the microscopic distribution of hydrate. In the middle stage, a large amount of hydrate decomposes, and the main factor affecting the acoustic wave velocity of hydrate in this stage is the change in hydrate content. In the later stage of hydrate dissociation, the hydrate distribution pattern consists mainly of the pore-filling type, and the hydrate micro-distribution at this stage is the main factor affecting the acoustic wave velocity. This study will be of great significance for understanding the microscopic control mechanism of hydrate reservoir geophysical exploration.

Research Progress on Global Marine Gas Hydrate Resistivity Logging and Electrical Property Experiments - Qiang Chen; Nengyou Wu; Changling Liu; Changchun Zou; Yang Liu; Jianye Sun; Yanlong Li; Gaowei Hu (Journal of Marine Science and Engineering, 2022)
Natural gas hydrate is widely spread in marine environments around the world. It has great energy potential due to its high methane gas content. High-precision exploration and evaluation of marine gas hydrate still face great challenges as it is affected by the complex reservoir control mechanisms and distribution characteristics. Resistivity is widely used in geophysical logging and theoretical research on gas hydrate-bearing reservoirs by utilizing the high sensitivity electrical response. In this paper, based on the examination of the global marine gas hydrate occurrences, resistivity logging results are summarized. Then the key remaining gas hydrate resistivity experimental concerns are reviewed. In summary, resistivity properties are a reliable means to derive the gas hydrate reservoir characteristics, despite the effect induced by the anisotropic properties of hydrate reservoirs and drilling technology. The overall resistivity change associated with the occurrence of pore filling gas hydrate in reservoirs are relatively small, and the specific value is affected by sediment lithology and hydrate saturation. On the other hand, fracture filling hydrate reservoirs have strong anisotropy, and massive hydrate occurrences (i.e., layers of gas hydrate with no sediment) section shows very high resistivity variation. Clay minerals are an important factor restricting the accurate estimation of gas hydrate saturations from in situ resistivity measurements. Many experimental studies have proposed the correction of Archie empirical formula, but widely representative models have not yet been developed. It is worth noting that more complex resistivity measurements may be able to provide additional electrical response information on various gas hydrate systems.

Pore-Scale Investigation of the Electrical Property and Saturation Exponent of Archie’s Law in Hydrate-Bearing Sediments - Jinhuan Zhao; Changling Liu; Chengfeng Li; Yongchao Zhang; Qingtao Bu; Nengyou Wu; Yang Liu; Qiang Chen (Journal of Marine Science and Engineering, 2022)
Characterizing the electrical property of hydrate-bearing sediments is essential for hydrate reservoir identification and saturation evaluation. As the major contributor to electrical conductivity, pore water is a key factor in characterizing the electrical properties of hydrate-bearing sediments. The objective of this study is to clarify the effect of hydrates on pore water and the relationship between pore water characteristics and the saturation exponent of Archie’s law in hydrate-bearing sediments. A combination of X-ray computed tomography and resistivity measurement technology is used to derive the three-dimensional spatial structure and resistivity of hydrate-bearing sediments simultaneously, which is helpful to characterize pore water and investigate the saturation exponent of Archie’s law at the micro-scale. The results show that the resistivity of hydrate-bearing sediments is controlled by changes in pore water distribution and connectivity caused by hydrate formation. With the increase of hydrate saturation, pore water connectivity decreases, but the average coordination number and tortuosity increase due to much smaller and more tortuous throats of pore water divided by hydrate particles. It is also found that the saturation exponent of Archie’s law is controlled by the distribution and connectivity of pore water. As the parameters of connected pore water (e.g., porosity, water saturation) decrease, the saturation exponent decreases. At a low hydrate-saturation stage, the saturation exponent of Archie’s law changes obviously due to the complicated pore structure of hydrate-bearing sediments. A new logarithmic relationship between the saturation exponent of Archie’s law and the tortuosity of pore water is proposed which helps to calculate field hydrate saturation using resistivity logging data.

Active Methanotrophs and Their Response to Temperature in Marine Environments: An Experimental Study - Jing Li; Xiaoqing Xu; Changling Liu; Nengyou Wu; Zhilei Sun; Xingliang He; Ye Chen (Journal of Marine Science and Engineering, 2021)
Aerobic methane (CH4) oxidation plays a significant role in marine CH4 consumption. Temperature changes resulting from, for example, global warming, have been suggested to be able to influence methanotrophic communities and their CH4 oxidation capacity. However, exact knowledge regarding temperature controls on marine aerobic methane oxidation is still missing. In this study, CH4 consumption and the methanotrophic community structure were investigated by incubating sediments from shallow (Bohai Bay) and deep marine environments (East China Sea) at 4, 15, and 28 °C for up to 250 days. The results show that the abundance of the methanotrophic population, dominated by the family Methylococcaceae (type I methanotrophs), was significantly elevated after all incubations and that aerobic methane oxidation for both areas had a strong temperature sensitivity. A positive correlation between the CH4 oxidation rate and temperature was witnessed in the Bohai Bay incubations, whereas for the East China Sea incubations, the optimum temperature was 15 °C. The systematic variations of pmoA OTUs between the Bohai Bay and East China Sea incubations indicated that the exact behaviors of CH4 oxidation rates with temperature are related to the different methanotrophic community structures in shallow and deep seas. These results are of great significance for quantitatively evaluating the biodegradability of CH4 in different marine environments.

Experimental Study on the Shear Band of Methane Hydrate-Bearing Sediment - Xiaobing Lu; Xuhui Zhang; Fangfang Sun; Shuyun Wang; Lele Liu; Changling Liu (Journal of Marine Science and Engineering, 2021)
The occurrence of a shear band is often thought as the precursor of failure. To study the initiation of shear banding in gas hydrate-bearing sediments, two groups of triaxial compression tests combined with a CT (computer tomography) scan were conducted by triaxial CT-integrated equipment under two confining pressures and seven hydrate saturations. The macro stress–strain curves and the corresponding CT scanning images of the micro-structure and the distribution of the components were obtained. The geometric parameters of the shear bands were measured based on the CT images at four typical axial strains, respectively. The distribution characteristics of soil particles, water, hydrate and gas were also analyzed. It is shown that the existence of methane hydrate changes the mechanical property of hydrate-bearing sediment from plastic failure to brittle failure when the hydrate saturation is over 13%, which occurs in the range of the tests in this paper. The peak of the deviatoric stress increases with the hydrate saturation. The shear band is in either a single oblique line or inter-cross lines depending on the hydrate saturation, the effective confining pressure and the initial distribution of the gas hydrate. Most of the shear band surfaces are not straight, and the widths of the shear bands are almost non-uniformly distributed.

The Variation of Microbial (Methanotroph) Communities in Marine Sediments Due to Aerobic Oxidation of Hydrocarbons - Jing Li; Changling Liu; Nengyou Wu; Xingliang He; Xiluo Hao; Feng Li; Ye Chen; Qingguo Meng (Journal of Ocean University of China, 2021)

Effect of Methane Gas on Acoustic Characteristics of Hydrate-Bearing Sediment-Model Analysis and Experimental Verification - Qingtao Bu; Gaowei Hu; Changling Liu; Jie Dong; Tongju Xing; Jianye Sun; Chengfeng Li; Qingguo Meng (Journal of Ocean University of China, 2021)

Small grain and semi-dwarf 3, a WRKY transcription factor, negatively regulates plant height and grain size by stabilizing SLR1 expression in rice - Jie Lan; Qibing Lin; Chunlei Zhou; Yakun Ren; Xi Liu; Rong Miao; Ruonan Jing; Changling Mou; Thanhliem Nguyen; Xingjie Zhu; Qian Wang; Xin Zhang; et al. (Plant Molecular Biology, 2020)

Study of the Surface Morphology of Gas Hydrate - Jianye Sun; Chengfeng Li; Xiluo Hao; Changling Liu; Qiang Chen; Daigang Wang (Journal of Ocean University of China, 2020)

Mechanical Properties of Methane Hydrate-Bearing Interlayered Sediments - Lin Dong; Yanlong Li; Changling Liu; Hualin Liao; Guoqi Chen; Qiang Chen; Lele Liu; Gaowei Hu (Journal of Ocean University of China, 2019)

Late onsets of tropical cyclones in the decaying years of super El Niño events - Zhiqiang Li; Runyu Zhang; Kai Liu; Changling Zheng; Zhikun Chen (Acta Oceanologica Sinica, 2019)

Undrained shear strength evaluation for hydrate-bearing sediment overlying strata in the Shenhu area, northern South China Sea - Yanlong Li; Gaowei Hu; Nengyou Wu; Changling Liu; Qiang Chen; Chen’an Li (Acta Oceanologica Sinica, 2019)

Uptake of Urea Nitrogen by Oocystis borgei in Prawn (Litopenaeus vannamei) Aquaculture Ponds - Mei Liu; Xianghu Huang; Rui Zhang; Changling Li; Binhe Gu (Bulletin of Environmental Contamination and Toxicology, 2018)

Influence of foraminifera on formation and occurrence characteristics of natural gas hydrates in fine-grained sediments from Shenhu area, South China Sea - ChengFeng Li; GaoWei Hu; Wei Zhang; YuGuang Ye; ChangLing Liu; Qing Li; JianYe Sun (Science China Earth Sciences, 2016)

Baseline sensitivity of natural population and resistance risk of Peronophythora litchii to four novel QoI fungicides - Yuxin Zhou; Lei Chen; Jian Hu; Pengfei Liu; Yu Zhang; Qingxiao Meng; Bin Li; Naiguo Si; Changling Liu; Xili Liu (European Journal of Plant Pathology, 2016)

Comparison of UV/hydrogen peroxide and UV/peroxydisulfate processes for the degradation of humic acid in the presence of halide ions - Xiaoyi Lou; Dongxue Xiao; Changling Fang; Zhaohui Wang; Jianshe Liu; Yaoguang Guo; Shuyu Lu (Environmental Science and Pollution Research, 2016)

Pore capillary pressure and saturation of methane hydrate bearing sediments - Shicai Sun; Changling Liu; Yuguang Ye; Yufeng Liu (Acta Oceanologica Sinica, 2014)

Experimental studies on the P-T stability conditions and influencing factors of gas hydrate in different systems - ChangLing Liu; YuGuang Ye; ShiCai Sun; Qiang Chen; QingGuo Meng; GaoWei Hu (Science China Earth Sciences, 2013)